2006
DOI: 10.1007/s00254-005-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater resources management under environmental constraints in Shiroishi of Saga plain, Japan

Abstract: ERRATUMThe online version of the original article can be found at http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…See, for example, Wang and Zheng (1996) and Jha et al (2009). Moreover, these studies have predicted the best withdrawal at all production wells in order to meet the yearly demand while avoiding land subsidence; that is, the objectives have a hydrologic nature, whereas the constraints have an economic or environmental nature (for example, see Don et al 2006). Finally, these studies have aimed at maximising the net benefits from groundwater recharge; that is, the objectives were economic in nature, and no constraints were considered.…”
Section: The Literature On Groundwater Managementmentioning
confidence: 99%
“…See, for example, Wang and Zheng (1996) and Jha et al (2009). Moreover, these studies have predicted the best withdrawal at all production wells in order to meet the yearly demand while avoiding land subsidence; that is, the objectives have a hydrologic nature, whereas the constraints have an economic or environmental nature (for example, see Don et al 2006). Finally, these studies have aimed at maximising the net benefits from groundwater recharge; that is, the objectives were economic in nature, and no constraints were considered.…”
Section: The Literature On Groundwater Managementmentioning
confidence: 99%
“…The equation that describes the three dimensional movement of groundwater of constant density through a porous earth material under equilibrium conditions is the partial differential equation (Don et al, 2006):…”
Section: Groundwater Flow Simulationmentioning
confidence: 99%
“…Simulation models are more effective when combined with optimization models whereby a set of management objectives are achieved in the midst of several environmental and socioeconomic constraints. Don et al (2006) for instance coupled a numerical simulation model with an optimization model to predict groundwater response to settlement and to determine the optimal safe yield for groundwater without violating physical, environmental and socio-economic constraints in the Shiroishi area in the Saga Plain in Japan. This model enabled them to determine the effects of climate and various pumping scenarios on the aquifer system.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater intrusion constitutes the main environmental problem facing coastal aquifers worldwide [6] [7]. It is shown that excessive groundwater exploitation in coastal area leads to seawater intrusion and influences the quality of the groundwater in aquifers [8] [9].…”
Section: Introductionmentioning
confidence: 99%